The Association Between Physical Activity, Including Physical Activity Intensity, and Fear of Falling Differs by Fear Severity in Older Adults Living in the Community. (14th September 2018) - Sawa, Ryuichi; Asai, Tsuyoshi; Doi, Takehiko; Misu, Shogo; Murata, Shunsuke; Ono, Rei
Abstract: Objectives: Fear of falling (FoF) is common in older adults. Physical activity decreases as FoF increases. However, this association between physical activity and FoF may vary depending on activity intensity. The current study was performed to explore the associations between FoF and step count, light-intensity physical activity (LPA), and moderate/vigorous-intensity physical activity (MVPA) in community-dwelling older adults. Methods: This cross-sectional observational study was held at a local community association center, with 242 older adults living independently in the community (mean age: 75.1 ± 5.4 years). FoF was defined using the Falls Efficacy Scale-International and categorized into three levels (low, moderate, and high). Physical activity was measured using a uniaxial accelerometer worn for 7 consecutive days, and by calculating daily step count, LPA, and MVPA, over this period. Results: Step count and physical activity intensity showed significant linear trends across FoF severity ( p < .01, respectively). High FoF decreased step count by approximately 2, 000 steps/day. Further, high FoF was significantly associated with short durations of both LPA and MVPA. In addition, moderate FoF was associated with decreased LPA duration, even after adjustment for confounding variables. Discussion: Physical activity decreased concomitantly with a rise in FoF severity. Moreover, the association between physical activity and FoF differed by physical activity intensity level in community-dwelling older adults. Further studies are needed to investigate the causal relationship between FoF and objective physical activity in this population.